2014
DOI: 10.1371/journal.pone.0086469
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNAs and Other Small RNAs in Prefrontal Cortex in Schizophrenia, Bipolar Disorder and Depressed Subjects

Abstract: Because of the role played by miRNAs in post-transcriptional regulation of an array of genes, their impact in neuropsychiatric disease pathophysiology has increasingly been evident. In the present study, we assessed microRNA expression in prefrontal cortex (Brodmann area 10) of a well-characterized cohort of major depressed, bipolar, and schizophrenia subjects (obtained from Stanley Neuropathology Consortium; n = 15 in each group), using high throughput RT-PCR plates. Discrete miRNA alterations were observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
124
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(141 citation statements)
references
References 37 publications
13
124
3
1
Order By: Relevance
“…Acute treatment with Dizocilpine decreased the levels of miR-219 in the prefrontal cortex, whereas inhibition of miR-219 action suppressed Dizocilpineinduced hyperlocomotion and stereotypies. Thus, elevated expression of miR-219 in the dorsolateral prefrontal cortex from schizophrenia patients (Beveridge et al, 2010;Smalheiser et al, 2014) is consistent with the NMDA receptor hypoactivity theory of schizophrenia (Miller and Wahlestedt, 2010). Manipulating the expression or activity of miR-219 may therefore provide a potential therapeutic tool for the treatment of schizophrenia.…”
Section: Mirnas In Schizophreniasupporting
confidence: 67%
See 1 more Smart Citation
“…Acute treatment with Dizocilpine decreased the levels of miR-219 in the prefrontal cortex, whereas inhibition of miR-219 action suppressed Dizocilpineinduced hyperlocomotion and stereotypies. Thus, elevated expression of miR-219 in the dorsolateral prefrontal cortex from schizophrenia patients (Beveridge et al, 2010;Smalheiser et al, 2014) is consistent with the NMDA receptor hypoactivity theory of schizophrenia (Miller and Wahlestedt, 2010). Manipulating the expression or activity of miR-219 may therefore provide a potential therapeutic tool for the treatment of schizophrenia.…”
Section: Mirnas In Schizophreniasupporting
confidence: 67%
“…Regulate pain behavior Pan, et al, (2014) CaMKIIγ Associated with Scz through regulating NMDA receptor signaling Kocerha, et al, (2009) Associated with Scz and BP as revealed by elevated expression in these patients Beveridge, et al, (2010), Smalheiser, et al, (2014) miR-132 p250GAP Promote dendritic development Impey, et al, (2010), Pathania, et al, (2012), Wayman, et al, (2008) MeCP2 Regulate dendritic morphology Klein, et al, (2007) Mediate the integration of newborn neurons Luikart, et al, (2011) Regulates synaptic plasticity & recognition memory Hansen, et al, (2013), Hansen, et al, (2010), Lambert, et al, (2010), Scott, et al, (2012 Santarelli, et al, (2011), Wong, et al, (2013 Associated with Scz as revealed by higher serum level in sporadic patients Shi, et al, (2012) Mellios, et al, (2009) Associated with Scz as revealed by higher serum level in sporadic patients Shi, et al, (2012) Cheng, et al, (2007) and Qurashi and Jin, 2010). This review will discuss recent progress on understanding the roles of miRNAs in normal brain development and the association of these miRNAs with neurodevelopmental diseases, specifically schizophrenia and bipolar disorder, two closely related disorders (Table 1).…”
Section: Camkiiγmentioning
confidence: 99%
“…If major depression is due to lack of reward, the analysis of molecular profiles in the nucleus accumbens from CUMS‐induced depression and resilience should help to figure out the role of the nucleus accumbens in major depression and resilience based on molecules analyzed. The alternations of certain genes have not been observed in previous analyses (Bai et al, 2014; Elizalde et al, 2010; Li et al, 2013; Liu et al, 2015; Moreau, Bruse, David‐Rus, Buyske, & Brzustowicz, 2011; Rajkowska et al, 2015; Smalheiser et al, 2012, 2011, 2014), including Cckar , Tshr , Kcnj5 , Alox12 , Slc17a6 , Per2 , Rtn4r , and Nrn1 . These genes in the nucleus accumbens may be newly working for major depression or resilience.…”
Section: Discussionmentioning
confidence: 79%
“…Like synaptosomes prepared from fresh mouse brain tissue, the human synaptosomes appear to have relatively intact RNA integrity as shown by RNA bioanalyzer profiling and gel electrophoresis, and show the expected enrichment in synaptic proteins and RNAs and depletion of nuclear markers (Smalheiser et al, 2014).…”
Section: Resultsmentioning
confidence: 96%
“…Although most studies of synaptosomes have utilized rodent or primate tissue, a score of studies have employed human samples derived from surgical specimens or postmortem brain. We recently described the isolation of synaptosomes from human postmortem prefrontal cortex to study the expression of synaptic microRNAs and other small RNAs in depression, schizophrenia and bipolar disorder (Smalheiser et al, 2014). This protocol alluded to methods and modifications that are scattered among several publications, and did not explain the reasons for the procedures chosen.…”
Section: Introductionmentioning
confidence: 99%